Analisis Penerapan Metode Full Costing dan Variabel Costing dalam Penetapan Harga Jual Jasa pada Yufi Beauty Lubuk Pakam - Hasbi Fauzan Insyirah; Wahyu Syarvina; Sugianto Sugianto (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the application of Full Costing, Variable Costing, and production cost control methods in determining service prices at Yufi Beauty Lubuk Pakam. The phenomenon studied is the practice of pricing that is still based on estimates without systematic cost calculations, thus potentially resulting in inaccurate prices. This study uses a qualitative approach with a case study design to understand the managerial practices of business actors in depth. Data were collected through semi-structured interviews, participant observation, and documentation, with informants consisting of business owners, operational managers, and employees selected using purposive sampling. The results of the study indicate that before the analysis was conducted, service selling prices were not based on structured cost accounting methods. Calculations using the Full Costing method produce higher prices because they include all fixed and variable costs, while Variable Costing provides simpler and more relevant information for short-term decisions. Furthermore, production cost control has not been formally implemented, indicated by the absence of cost recording, cost standards, and cost variance evaluation. This study concludes that the systematic application of costing and cost control methods is crucial for producing more accurate and rational pricing. These findings imply the importance of improving the understanding of cost accounting for service MSMEs. Further research is recommended to examine the implementation of cost control systems more broadly in various service sectors.